Immunohistochemical expression of vascular endothelial growth factor and matrix metalloproteinase-9 in radicular and residual radicular cysts - Patrícia Alvarez Ruiz; Orlando Ayrton de Toledo; Cassiano francisco Weege Nonaka; Leão Pereira Pinto; Lélia Batista de Souza (University of São Paulo, 2010)
OBJECTIVE: This study assessed and compared the immunoexpression of vascular endothelial growth factor (VEGF) and matrix metalloproteinase-9 (MMP-9) in radicular cysts (RCs) and residual radicular cysts (RRCs), relating them to the angiogenic index and the intensity of the inflammatory infiltrate. MATERIAL AND METHODS: Twenty RCs and 10 RRCs were evaluated by immunohistochemistry using anti-VEGF and anti-MMP-9 antibodies. The angiogenic index was determined by microvessel count (MVC) using anti-von Willebrand factor antibody. RESULTS: The expression of both VEGF and MMP-9 was higher in RCs than in RRCs. RCs and RRCs presented strong epithelial expression of VEGF, irrespective of the intensity of the inflammatory infiltrate. Lesions with strong expression of MMP-9 showed significantly higher number of immunopositive cells for VEGF (p<0.05) and higher MVC (p<0.05). Lesions with dense inflammatory infiltrate exhibited significantly higher MVC (p<0.05) and higher number of immunopositive cells for VEGF (p<0.05). There was a positive correlation between both MVC (p<0.05) and the quantity of immunopositive cells for VEGF (p<0.05), with intensity of the inflammatory infiltrate. In addition, it was observed a positive correlation between the number of immunopositive cells for VEGF and MVC (p<0.05). CONCLUSIONS: VEGF and MMP-9 might play important roles in the angiogenesis in RCs and RRCs. In these lesions, the expression of these molecules and the MVC is closely related to the intensity of the inflammatory infiltrate. The expression of VEGF in the epithelial lining of RCs and RRCs might be important for the enlargement of these lesions.